ECONOMIC ANALYSIS OF DIFFERENT IRRIGATION DEPTHS IN FORAGE SORGHUM CROPS - RODRIGUES DE SOUSA, PAULO GLEISSON; DE ARAÚJO VIANA, THALES VINÍCIUS; DE CARVALHO, CLAYTON MOURA; FIRMIANO DE SOUSA, JOSÉ DE PAULA; CAMPOS, KILMER COELHO; DE AZEVEDO, BENITO MOREIRA (International Journal of Maize & Sorghum, 2020)
The objective of this work was to evaluate the production costs and profitability indexes of sorghum crop for silage production under different irrigation depths. The work was conducted at the Federal Institute of Education, Science and Technology of Ceará (IFCE) – Umirim Campus, from September to December 2016. The treatments were arranged in 5 x 5 split plots with 5 replications. Irrigations were performed on a daily basis, and the applied depths were calculated based on crop evapotranspiration (ETc). The primary treatments were 50, 75, 100, 125 and 150% of ETc, associated with different levels of carnauba bagana mulch (0.00, 2.50, 3.75, 5.00, and 6.25 cm). Effective Operating Cost (EOC), Total Operating Cost (TOC), Gross Revenue (GR), Operating Profit (OP), Profitability Index (PI) and Break-Even Price (BEP) were estimated. According to the indicators analyzed, it was found that this is a promising crop within the different agricultural production schools, with favorable rates for the producer. The variety evaluated presents high resistance as to the water limitation factor, showing positive indicators such as break-even point below the average prices practiced in the region.